Synthesize and Characterization of Hydroxyapatite from Freshwater Snail Shell Sulcospira Sp. Proceed by Combination of Ball Milling and Heat Treatment - Fajri, Hidayatul; , Gunawarman; Affi, Jon; Putra, Rezky Syahemi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Hydroxyapatite is one of important material in orthopedic application because its features like human bone, and it has potential to replace metal and ceramic in implantation. Hydroxyapatite may get from waste which rich calcium like sea shell and snail shell. In this research, the characterization of raw materials of hydroxyapatite from freshwater snailshell (Sulcospira sp.) was investigated. The shell was milled with ball mill in 200 rpm during 15 minute with 4 steps. Between the milling was conducted heat treatment process at temperature 900°C for 4h. The shell powder was then sorted based on its roughness with siever machine. Powder characterization was done with Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX) and X-ray Diffraction (XRD). Result of this study show that the minimum size of powder about 67 µm and percentage of calcium in the powder is increased until 55%.